Histories of suicide : international perspectives on self-destruction in the modern world - Weaver, John C.; Wright, David, 1965- (University of Toronto Press, 2009)
Suicide is one of the leading causes of death worldwide, with more than one million fatalities each year. During the post-war period, the rate of completed suicides has risen dramatically, especially among young men and Aboriginal peoples living in the Western world. While this has naturally led to growing concern amongst health care practitioners and policy experts, relatively little is known about the history of attempted and completed suicide. Histories of Suicide is the first book to examine the history of suicide in diverse national contexts, including Japan, Scotland, Australia, Soviet Russia, Peru, United States, France, South Africa, and Canada, to reveal the different social, political, economic, and cultural factors that inform our understanding of suicide. This interdisciplinary collection of essays assembles historians, health economists, anthropologists, and sociologists, who examine the history of suicide from a variety of approaches to provide crucial insight into how suicide differs across nations, cultures, and time periods. Focusing on developments from the eighteenth century to the present, the contributors examine vitally important topics such as the medicalization of suicide, representations of mental illness, psychiatric disputes, and the frequency of suicide amongst soldiers. An illuminating volume of studies, Histories of Suicide is a fascinating examination of the phenomenon of self-destruction throughout different historical periods and nations.